Numerical Analysis of Combined Effect Hybrid Fibres and Fire Insulation on the Fire Resistance Performance of SCC Beams - Zitouni, Mohamed; Kada, Abdelhak; Lamri, Belkacem; Arruda, Mário Rui (Periodica Polytechnica Civil Engineering, 2024)
The use of self-compacting concrete in structural members has become increasingly prevalent in various construction applications. However, these structures are susceptible to one of the most hazardous disasters, which is the fire. This paper presents a numerical investigation of the fire resistance performance of self-compacting reinforced concrete (SCC) beams, as well as a parametric study to assess the impact of hybrid fibres and fire insulation on enhancing their performance under fire conditions. The study is conducted by developing a 3D finite element (FE) model using ANSYS software, where temperatures are applied according to the ISO834 standard fire. Geometric and material nonlinearities are considered in the evaluation of the behaviour of beams under fire conditions. The developed FE model is validated by comparing the predicted results with those of the experimental tests in literature. The fire resistance performance of SCC beams was compared with that of normal strength concrete (NSC) beams. The parametric study is conducted using three types of fire insulation, namely Tyfo WR-AFP, CAFCO 300, and Carboline Type-5MD. The results showed that SCC beam has lower fire resistance performance than the NSC beam. However, the incorporation of hybrid fibres allows a 17% improvement in the fire resistance of SCC beams. The use of fire insulations has increased the fire resistance time of SCC beams, and more particularly Carboline Type-5MD insulation with an increase of 28%. The combined use of hybrid fibres and fire insulation improved the fire resistance of SCC beams by 43%.